KONTRIBUSI LATAR BELAKANG PENDIDIKAN TERHADAP PERKEMBANGAN EKONOMI KELUARGA (ANALISIS KRITIS) - Ida Ayu Made Yuni Andari; Ida Bagus Alit Arta Wiguna; Srirahayu Puspawati (Waisya : Jurnal Ekonomi Hindu, 2023)
Education helps improve skills and knowledge, opens up employmentopportunities, improves quality of life, increases social awareness,and increases participation in society. The purpose of this study is tocritically analyse the contribution of educational background inimproving family economic growth. In this study using qualitativeresearch using a literature review approach with critical analysis. Inthis study found four things 1). The relationship between educationalbackground and economy in the eyes of the community, 2). Theweakness of education for underprivileged families. 3). Economicproblems for people who do not have education 4). The extent towhich education can improve the economic development of the family.5). The need for education and economy for financial progress. Thisresearch can be used as preliminary research so that furtherresearchers get more accurate results.